External Sector Reform and Public Enterprise Restructuring - Bhattacharya, Rina (IMF Working Papers; Working Paper, 2000)
This paper explores the linkages between external sector reforms and public enterprise restructuring, paying attention to the role of the financial sector in ensuring the success of these reforms in the context of a comprehensive medium-term structural adjustment program. It discusses the arguments made in the academic literature on this issue, and analyzes how some countries-namely Algeria, Egypt, and Poland-have tackled reforms in these areas.